An investigation of the heat generated during cyclic loading of ultra‐high performance concrete. Issue 1 (18th November 2019) - Tran, Ngoc Linh; Deutscher, Melchior; Scheerer, Silke
Abstract: In this paper, the mechanism of heat generation in concrete due to cyclic loading is studied, in which the development of load‐induced temperature is modelled using a heat transfer equation. The heat generation rate is theoretically determined and the calculation is experimentally validated. The influence of the maximum size of aggregate of concrete on the temperature development is also taken into account. It is shown that the load‐induced temperature is generated by conversion of dissipate energy, which mainly occurs at the interfacial transition zone between binders and concrete aggregates and can be described by the plastic work of concrete material.